Evaluation of pharmacokinetic properties and anaesthetic effects of propofol in a new perfluorohexyloctane (F6H8) emulsion in rats: a comparative study - Tsagogiorgas, Charalambos; Heesch, Elisabeth Sabine; Krebs, Jörg; Beck, Grietje; Yard, Benito A. (International journal of pharmaceutics, 2015)
Propofol (2,6-diisopropylphenol) is a safe and widely used anaesthetic, but due to low water solubility and high lipophilicity a difficult compound to formulate. The solubility of propofol in the semifluorinated alkane perfluorohexyloctane (F6H8) is very high (>300mg/ml). In the present work we investigate if a F6H8-based emulsion could be used as a new intravenous drug delivery system for propofol from a pharmacokinetic, pharmacodynamic and safety point of view. The pharmacokinetic parameters were evaluated after an intravenous bolus injection of either Disoprivan® or a F6H8-based propofol emulsion in Wistar rats. The onset and end of sedation after multiple dosings (5, 10 and 15mg/kg bw) were examined. Clinical chemistry and histology were assessed. No significant difference was found for any of the pharmacokinetic parameters. No differences in the onset nor the end of sedation in the tested dosages could be detected. Histology scores revealed no differences. A slightly increased alanine aminotransferase (ALT) was measured after multiple application of the F6H8-propofol emulsion. In conclusion, the F6H8-propofol emulsion showed no significant different pharmacokinetics and sedation properties, compared to a commercial soy-based propofol emulsion. Further, no toxic effects could be detected on the F6H8 emulsion indicating it was a safe excipient in rats.